Optimal antenna slot design for hepatocellular carcinoma microwave ablation using multi-objective fuzzy decision making - Nantivatana, Petch; Phasukkit, Pattarapong; Tungjitkusolmun, Supan; Chayakulkheeree, Keerati (My University, 2020)
This paper presents the optimal antenna slot position and sizing (OASPS), for microwave (MW) hepatocellular carcinoma (HCC) treatment, using multi-objective fuzzy decision making (MOFDM). In the optimal design problem formulation, the multi-objective for, (1) achievement for a near-spherical zone for ablation defined by axial ratio (AR), (2) the minimum reflection coefficient (S11), and (3) maximum volume of destroying (VD), are desired. The finite element method (FEM) is used for MW distribution simulation for coordination analysis with the proposed MOFDM based OASPS. The investigation on the design results shown that the temperature distribution of the proposed MOFDM for OASPS is in the more controllable shape comparing to the existing design, due to the sharp beam of temperature distribution to the target at the front side of slot with the less temperature distribution at the rare side of slot. The results also show that the proposed MOFDM for OASPS for OASPS design is easier to manage with the less effect to the rare side of the slot. Moreover, the proposed MOFDM for OASPS resulted in the temperature distribution shape closer to round shape than the existing design. The MOFDM for OASPS is tested on designing of the antenna build up from the coaxial cable. The coaxial cable used is Semi-rigid 141 (RG402 M17/130-RG402 Copper Jacket) including Inner conductor, Dielectric, and Outer conductor. In the simulation, the slot distance from conductor end (Lts), representing the slot position, is varied as 2.3mm, 3.3mm, 4.3mm, 5.3mm, 6.3mm, 7.3mm, and 8.3mm. Meanwhile, the slot size (Wd), is varied as 1mm, 2mm, 3mm, 4mm, 5mm, and 6mm. The input power (Pi) used is 50 W with the duration of 300 seconds. The comparison of obtained by different Lts and Wd, is investigated. The simulation results show that the proposed MOFDM based OASPS can efficiently and effectively provide the near-spherical zone of ablation result with simultaneously trade-off between S11 minimization and VD maximization.
Keywords: Finite element method; Hepatocellular carcinoma treatment; Microwave ablation; Multi-objective fuzzy decision making